Design and Optimization of the Quad-Band Negative Group Delay Circuit Based on Genetic Algorithm - Duan, Jiashuai; Zhang, Li (Asia-Pacific International Symposium on Electromagnetic Compatibility, 2022)
In this paper, a new low-loss quad-band microwave negative group delay circuit (NGDC) based on coupled microstrip lines is presented. The circuit is mainly composed of a transmission line coupled with three groups of symmetrically coupled microstrip lines. In order to increase the absolute value of the negative group delay (NGD) at each frequency point, Genetic Algorithm is chosen to optimize the NGDC, and the NGD result has been significantly improved. Through physical processing and testing, the experimental results are in good agreement with the simulation results, which proves the quad-band NGD characteristics of the circuit and the feasibility of GA to optimize NGDC. Experimental results show that at 6.74GHz, 7.13GHz, 9.97GHz and 11.20GHz, the negative group delay values are -3.8ns, -2.7ns, -3.8ns and -5.4ns, respectively.